Social Environments and Physical Activity Among Active Black Women. Issue 8 (November 2022) - Affuso, Olivia; Kinsey, Amber W.; Whitt-Glover, Melicia C.; Segar, Michelle; Bowen, Pamela
Purpose: To explore the social context of physical activity (PA) among active Black women, we examine the patterns of PA engagement and the benefits of social support in PA maintenance. Design: A cross-sectional study design and descriptive phenomenological approach were used to examine social support and lived experiences of active Black women. Setting: The study setting was an online survey of active Black women, ages 21 to 71 years who were recruited from across the United States. Participants: This secondary data analysis was conducted among a sample of 187 active Black women who maintained PA for ≥6 months. The mean age was 41 ± 12.3 years, 83.4% completed some college, 37.7% were married, and 30.0% had children. Measures: Participants self-reported 'with whom' they engaged in PA and provided qualitative responses about their strategies for PA maintenance. Descriptive statistics were used to examine between-group differences among demographic characteristics and PA variables by category of PA engagement using SAS 9.4. Descriptive phenomenology was used to explore social support themes across and within categories of PA engagement. Results: On average, the active Black women in this study reported engaging in 57.0 ± 18.9 minutes of moderate intensity leisure-time PA per session. Most engaged in PA alone (n = 87), with a group (n = 72), or with another individual (n = 28). Social context themes within categories included: alone – self-management, groups - motivation and accountability, family – values health, and friends – shared interests in PA . Subthemes across social context categories included: who? - people, what and how? - types of social support, and where? – place of social support . Conclusions: Our findings suggest that some Black women may need added social support from others beyond family and friends, while other Black women may prefer additional self-management skills. Nonetheless, this study provides data for developing hypotheses about the mechanisms by which social context may facilitate PA maintenance among Black women. Therefore, intervention studies targeting PA maintenance among Black women should include an in-depth query of social support needs.